2022
DOI: 10.3390/antiox11081571
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Autophagy for Developing New Therapeutic Strategy in Intervertebral Disc Degeneration

Abstract: Intervertebral disc degeneration (IVDD) is a prevalent cause of low back pain. IVDD is characterized by abnormal expression of extracellular matrix components such as collagen and aggrecan. In addition, it results in dysfunctional growth, senescence, and death of intervertebral cells. The biological pathways involved in the development and progression of IVDD are not fully understood. Therefore, a better understanding of the molecular mechanisms underlying IVDD could aid in the development of strategies for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 363 publications
0
3
0
Order By: Relevance
“…Immunofluorescence analysis revealed that the fluorescence intensity of DDIT4 was enhanced in NPCs treated with H 2 O 2 ( Figure 2c ). Western blotting showed that increased expression of DDIT4 in H 2 O 2 -treated NPC in a concentration-dependent manner was accompanied by a decrease in two important ECM-associated proteins, 33 COL2A1 and ACAN, and an increase in MMP13 and ADAMTS5, which are involved in the degradation of the ECM ( Figures 2d to 2i ). 34 To explore pyroptosis in NPCs under oxidative stress, the expression of NLRP3, ASC, cleaved GSDMD, cleaved CASP1, and IL-1β increased in a concentration-dependent manner in H 2 O 2 -treated NPCs (Supplementary Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…Immunofluorescence analysis revealed that the fluorescence intensity of DDIT4 was enhanced in NPCs treated with H 2 O 2 ( Figure 2c ). Western blotting showed that increased expression of DDIT4 in H 2 O 2 -treated NPC in a concentration-dependent manner was accompanied by a decrease in two important ECM-associated proteins, 33 COL2A1 and ACAN, and an increase in MMP13 and ADAMTS5, which are involved in the degradation of the ECM ( Figures 2d to 2i ). 34 To explore pyroptosis in NPCs under oxidative stress, the expression of NLRP3, ASC, cleaved GSDMD, cleaved CASP1, and IL-1β increased in a concentration-dependent manner in H 2 O 2 -treated NPCs (Supplementary Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…Studies of degenerative rat NPCs have reported increased autophagy activity and up-regulation of autophagy-related genes compared with healthy disc tissue. 42 Recovery of autophagy flux can salvage oxidative damage and mitochondrial dysfunction to prevent disc degeneration. 43 Multiple studies have linked mitophagy to the initiation and development of disc degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy initiation has been suggested to protect against apoptosis in IVDD, underscoring its cytoprotective role [33,34]. While current research predominantly supports autophagy's preventive role in IVDD, some studies suggest its potential to accelerate the condition [35]. Autophagy reduces NP cell apoptosis, ECM degradation, senescence, and CEP inflammation and calcification, maintaining IVD ECM balance to prevent IVDD [36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%